The Influence of Leadership Style and Work Motivation of School Principals on the Pedagogical Competence of Elementary School Teachers - Karlina, Iin; Wijayanti, Wiwik (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This research aims to determine the partial and simultaneous influence of the principal's leadership style and work motivation on teachers' pedagogical competence. The method used in this research is quantitative with a causal associative type of research. The sample in this study consisted of three schools, namely Klitren State Elementary School, Samirono State Elementary School, and Demangan State Elementary School, totalling 42 teachers. The instrument used in this research was a questionnaire. Data collection techniques by distributing questionnaires to elementary school-level teachers. Data analysis techniques use multiple linear regression, t-test, F test and coefficient of determination test. The research results show a significant and positive influence partially and simultaneously between the variables of leadership style and work motivation of school principals on teachers' pedagogical competence. With the support of the school principal's leadership style and motivation, teachers can improve their pedagogical competence because they can provide guidance, information and facilities in the learning process.